Autoantibody Profile and Lung HRCT Scan in Systemic Sclerosis with Restrictive Lung Disease - Saragih, Winda Agnestia Maranna; Dewi, Sumartini; Wachjudi, Rachmat Gunadi; Logito, Verina; Tjandrawati, Anna (Faculty of Medicine Universitas Padjadjaran, 2023)
Objective: To identify auto-antibodies in systemic sclerosis with interstitial lung disease (ILD). Method: This was a descriptive categorical study on auto-antibody profile in systemic sclerosis patients visiting the Rheumatology Clinic of Dr. Hasan Sadikin General Hospital, West Java, and Bandung during the period of January 2018 to December 2019 who were registered in the West Java Systemic Sclerosis Registry. Auto-antibody identification was performed using the Euroline immunoblot assays.Results: Thirty six cases were identified during the study period with most of the cases involved women (n=35, 97.2%). The average age of patients participating in this study was 40 years, with an average duration of disease of 18 months. Diffuse cutaneous systemic sclerosis was found in 22 (61.1%) cases and limited cutaneous systemic sclerosis was observed in 14 (38.9%) cases. Specific autoantibodies were positive in 33 (91.6%) cases, with anti-topoisomerase I as the largest group, positive in 22 (52.9.3%) cases. This was followed by anti-Th/To in eight (15.7%) cases; anti-Ro52 in four (7.8%) cases; anti-centromere in three (5.9%) cases; anti-RNA polymerase in three (5.9%) cases; anti-fibrillarin in three (5.9%) cases; anti-Ku in two (3.9%) cases; and anti-PDGF in one (2.0%) case. High-resolution computed tomography of the lung showed 34 (94.4%) cases with ILD and 22 (61.1%) cases with severe lung fibrosis. Usual interstitial pneumonia was seen in 19 (52.8%) cases and non-specific interstitial pneumonia in 15 (41.7%) cases.Conclusion: Anti-topoisomerase I, anti-Th/To, and anti-Ro52 are the most common autoantibodies observed in systemic sclerosis patients with ILD as the most prevalent feature detected with lung HRCT.